Lama post operasi Coronary Artery Bypass Graft (CABG) dengan kualitas hidup pasien post operasi CABG di RSPAD Gatot Soebroto - Titik Suyanti; Sri Rahayu (Universitas Baiturrahim, 2020)
AbstractCoronary heart disease (CHD) can be treated with Coronary Artery Bypass Graft (CABG). This procedure is expected to reduce the morbidity and mortality rates due to CHD, and able to improve the quality of life. However, the recovery time of patients with post-operative CABG requires time to achieve a better quality of life. This study aims to determine the relationship between the length of postoperative CABG with the quality of life of post-operative CABG patients in Gatot Soebroto Army Hospital. The research method used a descriptive quantitative with a cross-sectional approach with a sample of 31 post-operative CABG patients who were willing to be respondents. Total sampling was used in this study. The instrument used a WHOQOL-BREF questionnaire that was valid and reliable. The results showed that the characteristics of patients with post-operative CABG were mostly 14 people (45.2%) aged 50-59 years old, 25 people (80.6%) were male, 16 people (51, 6%) were high school, and 15 people (48.4%) not working, 15 people (48.4%) have a length of post-operative CABG 4-6 months, and 21 people (67.7%) have a good quality of life. The results of the bivariate analysis with the Chi-square test showed that there was a relationship between the length of postoperative CABG with the quality of life of patients with a p-value = 0.006. The conclusion is encouraging the patients, families, and health workers, especially nurses have to pay attention to the quality of life of patients based on the length of post-operative CABG. Because of the length of post-operative CABG the better the quality of life of patients.